An Evaluation Of Healthcare Expenditure Policies And Development Of A University-Based Sustainable Healthcare Financing Model - Al-Shami, Abdulkareem Mohammed Ahmed (2017)
Escalation of healthcare cost is a world-wide problem. Assessing and improving the healthcare financing system should be a part of any agenda for healthcare reforms. To balance the current health accounts, especially in the case of deficit, three variables can be considered- the government subsides, the co-payment and the contribution rate of the insurance. In this thesis, evaluations for health care financing system at University Sains Malaysia (USM) and simulation model were used to address the issues in the current USM healthcare financing system. Then, examine a number of alternative scenarios using health insurance simulation model “SimIns”, by paying special attention to forecasted changes in health expenditure and feasibility of financing those changes.